SPECYFIKA DYSKURSU O REWOLUCJI LUTOWEJ NA ŁAMACH „ŚWIATA” W 1917 ROKU - Gabryś-Sławińska, Monika (Przegląd Wschodnioeuropejski, 2024)
The purpose of the article is to reconstruct the unique discourse related to the February Revolution as presented in the Warsaw weekly magazine “Świat” in 1917. The analysis focuses on the issues published between March (the outbreak of the February Revolution) and the beginning of July (the last reports) of 1917, taking into account both verbal messages and the iconographic layer of the periodical. The research revealed that the editorial team adopted a strategy of contextualizing contemporary developments within the past events. Profiling the coverage in this way offered readers a structured narrative, in which the violence and chaos of the contemporary world were replaced by a problematizing approach that minimized the anxiety associated with the revolution. The verbal content was correlated with the iconographic layer, allowing the editors to portray the February Revolution as part of an evolutionary process.